2019
DOI: 10.1038/s41598-019-50989-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CT morphologic features and attenuation for differentiating among transient lesions, atypical adenomatous hyperplasia, adenocarcinoma in situ, minimally invasive and invasive adenocarcinoma presenting as pure ground-glass nodules

Abstract: Thin-section computed tomography (TSCT) imaging biomarkers are uncertain to distinguish progressive adenocarcinoma from benign lesions in pGGNs. The purpose of this study was to evaluate the usefulness of TSCT characteristics for differentiating among transient (TRA) lesions, atypical adenomatous hyperplasia (AAH), adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA) and invasive adenocarcinoma (IAC) presenting as pure ground-glass nodules (pGGNs). Between January 2016 and January 2018, 255 pG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
3
18
1
Order By: Relevance
“…Patients with IAC tended to be older, while patients with MIA were younger. This was consistent with previous findings [ 28 ]. Morphological features from CT images are frequently used in routine clinical practice for the ADC with pGGNs differential diagnostic process [ 29 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Patients with IAC tended to be older, while patients with MIA were younger. This was consistent with previous findings [ 28 ]. Morphological features from CT images are frequently used in routine clinical practice for the ADC with pGGNs differential diagnostic process [ 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…Patients with IAC tended to be older, while patients with MIA were younger. This was consistent with previous findings [28]. Morphological features Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Pulmonary GGN is an early manifestation of various benign and malignant lesions; thus, early diagnosis determines the way of treatment, which influences the patients' prognosis [1,[16][17][18][19]. Several studies have revealed that benign and malignant GGNs can be distinguished according to their specific CT morphological features, such as the size, lobulation, spiculation, vacuoles, pleural traction, and air bronchogram sign [17,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“… 9–12 There have been several studies of the CT features of absorbable nodules, but most of them have focused on part-solid nodules. 5 , 13–17 …”
Section: Introductionmentioning
confidence: 99%